Maestría en Educación Rural: una propuesta innovadora - Carvajal Jiménez, Vivian (2007)
This article is about the Graduate Program in Rural Education that started in 2006. This program is an innovative experience because it is developed in two different modalities: face to face and distance with virtual components.It includes five different modules; each one developed in a different Central American country. The participants are from all over Central America. The author explains, how this is an original alternative from the Rural Education Department (DER) of the Center of Investigation and Teaching in Education (CIDE) to the national and international community, that supports people who is interested and linked with the development of rural areas in the region.